Interest in Local Wisdom-Based Entrepreneurship among High School Students - Susanti, Eka Nana (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Urban entrepreneurship education generally emphasizes generic commercial models that are irrelevant to students' cultural contexts. In Jakarta, Betawi cultural values and the local creative economy are underutilized to nurture entrepreneurial spirit, missing an opportunity to build true and sustainable business interest. This study intends to analyze the effectiveness of a program designed to strengthen entrepreneurial interest based on local wisdom among high school students in Jakarta by integrating Betawi cultural values and local creative economy practices. The research employed a quantitative approach with a quasi-experimental, pretest-posttest control group design. The sample consisted of 120 11th-grade students selected through cluster random sampling across Jakarta. Research instruments included a validated entrepreneurial interest questionnaire, structured observations of learning activities, and performance assessment sheets for local product-based projects. The findings indicated that the experimental group had a much higher level of interest in entrepreneurship than the control group (p < 0.05). The findings reveal that integrating local wisdom enhances material relevance and significantly strengthens students' cultural identity and creativity in developing business ideas. When business concepts connected to their immediate cultural heritage, like Betawi traditions, students demonstrated increased engagement. This study provides an empirical framework for urban "Indigenous Entrepreneurship" in vocational and secondary education. Policymakers and educators should implement curricula based on local potential to increase entrepreneurial temperament and preserve cultural heritage among urban kids.